The Secret Life of ACE2 as a Receptor for the SARS Virus - Dimitrov, Dimiter S (Cell, 2003)
The membrane-associated carboxypeptidase angiotensin-converting enzyme 2 (ACE2) is an essential regulator of heart function. Now, Li at al. identify and characterize an unexpected second function of ACE2 as a partner of the SARS-CoV spike glycoprotein in mediating virus entry and cell fusion.